Leitura e escrita no final do ciclo de alfabetização: uma interface com a proposta de letramento do PNAIC - Fontes, Geysa Paula Castor da Silva (2015)
This paper presents the results of a research that aimed to analyze the development of the literacy final circle students in reading and writing by applying a didactic proposal-driven by the material of PNAIC - Pacto Nacional pela Alfabetização na Idade Certa (National Pact for Literacy at Age One) (BRAZIL, 2012). The research was developed from our own experience of teaching in a public school classroom located in Bayeux-PB, with students aged between eight and eleven, in order to assess the benefits of literacy proposal for alphabetize these students. This work has an investigative and qualitative-quantitative nature, and is also descriptive and interventional. Our research is theoretically based on Soares and Soares (2010, 2011), Tfouni (2010), Kleiman (2008), Solé (2009), Leffa (1996), Chartier (2007), among others, and was developed in three stages: 1) verification of the quantitative class in relation to reading and writing skills of students from the bimonthly monitoring sheet of the first six months; 2nd) application of didactic proposal containing sequential activities to improve students' knowledge regarding the reading and writing; 3rd) Performance analysis of students the end of the application of the intervention proposed and new quantitative verification of the class recorded in the accompanying form of the first eight months. The material obtained during the application of didactic proposal as well as the bimonthly monitoring sheets of PNAIC are the corpus of this work. From the verification of the evaluation sheet records the PNAIC of the first six months, we identified that large portion of the class still facing difficulties in reading and writing learning, and based on literacy perspective proposed by the PNAIC itself, we structured composed material of several integrated activities into the worldly wisdom of students and playful character to work with these difficulties. After the development of intervention proposal, we verified through the analysis of the material itself and then the first 8 months bimonthly monitoring sheet, some students made a breakthrough in relation to reading and writing skills. The results achieved highlight the importance of literacy perspective on alphabetization presented by the National Pact for Literacy at the Age One.